Implementation of Religious Culture to Develop Children’s Character in Early Childhood Education - Pamuji, Zuri; Roqib, Moh.; Basit, Abdul; Yahya, M. Slamet (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
Efforts to develop children's character based on the application of religious culture are important for every early childhood education institution, but the implementation patterns are still limited. This research aims to describe the application of religious culture in early childhood education institutions in cultivating character to find application patterns. This research uses a qualitative descriptive method with a single case study design conducted at one of the early childhood education institutions in Banyumas, Indonesia. Data search was carried out using interviews, observation, and documentation. Analysis techniques used, data reduction, data presentation, verification, and conclusion. The research results show that the application of religious culture has two main parts. The part related to the phasing pattern of cultivating religious values and the part related to various religious cultures and how to transmit them to children. The phasing pattern of cultivating religious values in children is carried out through introduction and training, which leads to habituation. Meanwhile, various religious cultures include cultures related to holy books, religious rituals, and places of worship. Religious culture is transmitted through the learning process and activities outside the learning process, including socialization, role modeling, and building communication between parents and institutions. Keywords: religious culture, character, early childhood References: Abdurohim, Rohimah, B., & Hayani, R. A. (2021). Fungsi Ibadah Ritual Dalam Pembentukan Karakter Islami. Jurnal Pendidikan Karakter